Penerapan model Problem Based Learning dalam pembelajaran daring untuk meningkatkan hasil belajar siswa kelas VI di SD Negeri Mulyasari 03 - Tri Julianto (Perkumpulan Kualitama Edukatika Indonesia, 2020)
This study aims to improve the learning outcomes of Grade VI students at SD Negeri Mulyasari 03 by applying the Problem Based Learning Model in Online Learning as an effort to improve and enhance the learning process. The research method used was Classroom Action Research, which included planning, acting, observing, and reflecting. The research was conducted in two cycles, each cycle carried out two meetings. The results showed that student learning outcomes improved. In the initial study, the average value was 67.08 with KKM 70 completeness of learning 18.51% after the implementation of the learning improvement in cycle I, the average knowledge value reached 76.67 and the percentage of completeness reached 66.77% and not yet completed 33.23 %. The attitude score for the very good category reached 29.17% and the good category reached 70.83%, and the average skill score reached 69.58 while the percentage of completion reached 54.17% and 45.83% incomplete. In the second cycle, it was found that the average knowledge value reached 77.08 and the percentage of completeness reached 87.50% and 13.50% incomplete. The attitude score of the very good category reached 41.67% and the good category reached 58.33%. The average skill score reached 72.08, while the percentage of completion reached 83.33% and 16.67% unfinished. Based on the data obtained, it can be concluded that using the Problem Based Learning model can improve the learning outcomes of grade VI students at SD Negeri Mulyasari 03, Majenang District.